Key techniques for precise measuring gas content in deep coal mine: In-situ pressure- and gas-preserved coring - Ju Li; Jianan Li; Tianyu Wang; Guikang Liu; Zhiqiang He; Cong Li; Heping Xie (International Journal of Mining Science and Technology)
Gas content serves as a critical indicator for assessing the resource potential of deep coal mines and forecasting coal mine gas outburst risks. However, existing sampling technologies face challenges in maintaining the integrity of gas content within samples and are often constrained by estimation errors inherent in empirical formulas, which results in inaccurate gas content measurements. This study introduces a lightweight, in-situ pressure- and gas-preserved corer designed to collect coal samples under the pressure conditions at the sampling point, effectively preventing gas loss during transfer and significantly improving measurement accuracy. Additionally, a gas migration model for deep coal mines was developed to elucidate gas migration characteristics under pressure-preserved coring conditions. The model offers valuable insights for optimizing coring parameters, demonstrating that both minimizing the coring hole diameter and reducing the pressure difference between the coring-point pressure and the original pore pressure can effectively improve the precision of gas content measurements. Coring tests conducted at an experimental base validated the performance of the corer and its effectiveness in sample collection. Furthermore, successful horizontal coring tests conducted in an underground coal mine roadway demonstrated that the measured gas content using pressure-preserved coring was 34% higher than that obtained through open sampling methods.